Eye Care: Do you Really Care? Eye Care Trends in Critical Care Units in the year 2021 - ., Chandni; John, Minimol; Sebastian, Susan; ., Himanshi; Gangmei, Bibiana Niamchungmei (Research & Review: Management of Emergency and Trauma Nursing (e-ISSN: 2582-0494), 2022)
Eye care is a fundamental procedure in nursing. Delays and failure to identify the complications of eye with patient on ventilators or inadequate eye care of ventilated and unconscious patients in ICUs may result in increased complications, increased length of hospital stay, eye injuries or infections. As nurse’s primary concern is saving patients, this process has been overlooked. In ICUs the incidences and risk factors of corneal injury are neglected these days. As we are in the era where there is an increase in ICU nursing workload involving not only medical & surgical issues but fullblown cases of COVID-19 patients, its complications, and the increasing prevalence of prone positioning among this patient group. Researcher proceeded with a quantitative descriptive research approach with nurses(n=72) to evaluate the current knowledge and practice of intensive care unit (ICU) nurses which aimed at providing guidance and information to clinical staff, protecting the eye of vulnerable patients in order to prevent ICU-related eye problems, identifying patients who might need eye referral so that early intervention could be initiated, and to formulate the guidelines & SOPs of eye care for ICU patients. In assessing both knowledge and eye care skills in the ICU, the researchers used a Likert scale with a five-point scale and an expressed practices checklist. Structured questionnaire was designed to assess the pre & post knowledge. Majority (87.5%) of the nurses had not attended eye training courses. A major barrier to eye care practice was the lack of education and Eye care perceived as low priority, which accounted for 81.94% of participants. Participants reported being satisfied with the education overall after the program, and all nurses indicated a plan to change their existing eye care practices. In the ICU environment, nurses' knowledge of eye care and eye care procedures increased significantly after educational intervention. The mean posttest knowledge (72) of staff nurses of ICU was higher than the mean pretest knowledge scores (4.80) with a mean difference of 12.54. The ‘z’ value of 25.26 at was found to be statistically significant at 0.05 level Therefore Researcher highly recommended for Eye care which should be a routine care for the critically ill patient in the ICU and it should be prioritized as first activity in basic hygiene care. Guidelines & SOP’s related to Eye care and its Referral pathways need to be incorporated in ICU Manuals.so as to ensure that information regarding Eye care is appropriate. Intensive care unit Patients should have access to consistent, high-quality eye care. This should be recorded in nursing records.